2021
DOI: 10.3390/cancers13143439
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis or Granulocyte-Colony Stimulating Factor Support in Multiple Myeloma Patients Undergoing Autologous Stem Cell Transplantation

Abstract: We compare, in this manuscript, antibiotic prophylaxis versus granulocyte-colony stimulating factor (G-CSF) support as anti-infective strategies, in patients with multiple myeloma (MM), undergoing high-dose therapy followed by autologous stem cell transplantation (HDT/ASCT). At our institution, antibiotic prophylaxis after HDT/ASCT in MM was stopped in January 2017 and replaced by G-CSF support in March 2017. Consecutive MM patients who received HDT/ASCT between March 2016 and July 2018 were included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Also studied were three non-fermenters with 5/144 (3%) studies about Acinetobacter baumannii [82,[140][141][142][143], 4/144 (3%) studies about Pseudomonas aeruginosa [83,84,144,145], and 5/144 (3%) studies about Stenotrophomonas maltophilia [85][86][87][88]146], often specified as either multidrug-or extensively drug-resistant. We also found several studies focusing on four well-known healthcare-associated bacteria, with 11/144 (8%) focusing on VRE [89][90][91][92][93][94][95][96][97][98]147,148], 7/144 (5%) focusing on carbapenemase-producing K. pneumoniae (KPC) [99][100][101][102][149][150][151], 2/144 (1%) focusing on methicillin-resistant Staphylococcus aureus (MRSA) [42,152], and 6/144 (4%) focusing on extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-E) [103,104,[153][154][155][156]. We also found that fungi typically resistant to antifungals were studied, 3/144 (2%) studies about Aspergillus spp.…”
Section: Study Characteristicsmentioning
confidence: 73%
See 1 more Smart Citation
“…Also studied were three non-fermenters with 5/144 (3%) studies about Acinetobacter baumannii [82,[140][141][142][143], 4/144 (3%) studies about Pseudomonas aeruginosa [83,84,144,145], and 5/144 (3%) studies about Stenotrophomonas maltophilia [85][86][87][88]146], often specified as either multidrug-or extensively drug-resistant. We also found several studies focusing on four well-known healthcare-associated bacteria, with 11/144 (8%) focusing on VRE [89][90][91][92][93][94][95][96][97][98]147,148], 7/144 (5%) focusing on carbapenemase-producing K. pneumoniae (KPC) [99][100][101][102][149][150][151], 2/144 (1%) focusing on methicillin-resistant Staphylococcus aureus (MRSA) [42,152], and 6/144 (4%) focusing on extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-E) [103,104,[153][154][155][156]. We also found that fungi typically resistant to antifungals were studied, 3/144 (2%) studies about Aspergillus spp.…”
Section: Study Characteristicsmentioning
confidence: 73%
“…Hefazi et al found that VRE colonisation is associated with VRE infection in stem cell transplantation patients and Ramanan et al found that VRE colonisation pre-transplantation was associated with any infection post-transplantation (31, 88). Heisel et al found that cephalosporin use and intravenous vancomycin were associated with VRE infections in patients with acute myeloid leukaemia or myelodysplastic syndrome undergoing intensive induction therapy, and finally Klein et al found that in multiple myeloma patients, granulocyte-colony stimulating factor was associated with fewer VRE cases than antibiotic prophylaxis (89, 90).…”
Section: Resultsmentioning
confidence: 99%
“…Hefazi et al found that VRE colonisation is associated with VRE infection in stem cell transplantation patients and Ramanan et al found that VRE colonisation pre-transplantation was associated with any infection post-transplantation [ 35 , 92 ]. Heisel et al found that cephalosporin use and intravenous vancomycin were associated with VRE infections in patients with acute myeloid leukaemia or myelodysplastic syndrome undergoing intensive induction therapy, and finally, Klein et al found that in multiple myeloma patients, granulocyte-colony stimulating factor was associated with fewer VRE cases than antibiotic prophylaxis [ 93 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the use of antibiotic prophylaxis, an overall consensus was not obtained, although most clinical immunologists had an opinion against the use of antibiotics for the prophylaxis of infections, except in cases of recurrent infections (excluding Pneumocystis carinii and viruses). In this context, in a recent study in a large cohort of patients with MM and autologous bone marrow transplantation, the use of antibiotic prophylaxis was associated with a higher risk of multidrug-resistant bacteria with respect to colony growth factors [36].…”
Section: Discussionmentioning
confidence: 99%